2022
DOI: 10.24018/ejbmr.2022.7.6.1711
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Liquidity in Determining Firm Performance: An Empirical Study on Manufacturing Companies in Indonesia

Abstract: This study aims to examine the role of liquidity in influencing firm performance, especially for manufacturing companies operating in Indonesia. The research variables include firm performance as the dependent variable, capital structure and firm size as independent variables, operating assets as a control variable, and liquidity as a moderating variable. The study was conducted on 123 manufacturing companies in Indonesia for the 2019-2021 period. The data collection method used purposive sampling, while the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Mukhibad et al (2020) and Djazuli & Dodi (2020) further emphasized the negative impact of liquidity on debt policy and the significant effect of liquidity, solvency, and profitability on dividends. Sudiyatno & Suwarti (2022) and Laurencia & Amalia (2020) both found that liquidity plays a significant role in firm performance, with the former also highlighting the influence of capital structure and firm size. Rizal et al (2020) and Simorangkir & Adamanti (2010) focused on the impact of fiscal and monetary policies, with the former finding a positive impact on macroeconomic performance and the latter emphasizing the effectiveness of a combination of fiscal and monetary expansion.…”
Section: Introductionmentioning
confidence: 98%
“…Mukhibad et al (2020) and Djazuli & Dodi (2020) further emphasized the negative impact of liquidity on debt policy and the significant effect of liquidity, solvency, and profitability on dividends. Sudiyatno & Suwarti (2022) and Laurencia & Amalia (2020) both found that liquidity plays a significant role in firm performance, with the former also highlighting the influence of capital structure and firm size. Rizal et al (2020) and Simorangkir & Adamanti (2010) focused on the impact of fiscal and monetary policies, with the former finding a positive impact on macroeconomic performance and the latter emphasizing the effectiveness of a combination of fiscal and monetary expansion.…”
Section: Introductionmentioning
confidence: 98%
“…Variabel penelitian meliputi kinerja perusahaan sebagai variabel dependen, struktur modal dan ukuran perusahaan sebagai variabel independen, aset operasi sebagai variabel kontrol, dan likuiditas sebagai variabel moderasi. Penelitian dilakukan terhadap 123 perusahaan manufaktur di Indonesia untuk periode 2019-2021 (Sudiyatno & Suwarti, 2022).…”
unclassified